Financial Inclusion and Refugees’ Self-Reliance: An Assessment for Women’s Economic Empowerment at Nakivale Refugee Settlement, Southwestern Uganda. - Mugisha, Abbas; Kaaya, Siraje (Kabale University, 2023)
The study examines the role of financial inclusion to women refugees’ self-reliance in Nakivale settlement. While self-reliance and economic inclusion are increasingly centralized in the international refugee regime as tools of empowerment that benefit women refugees, policy makers largely fail to consider the distribution and availability of local resources in promoting these ideas. Women refugees are often identified as passive and vulnerable victims of violence in need of support and remain disadvantaged in various socio-economic aspects. Nakivale settlement is not well suited for refugees’ economic independence due to the area’s land scarcity and social conflict. Employing qualitative methods, the study established economic challenges faced by women refugees and identified ways of solving socio-economic challenges that affect women refugees. The study recommends that creating credit facilities to enterprising women refugees will encourage trade within and outside the settlement and this could reduce vulnerability while improving the economy of the refugees and host community. The study concludes that since the majority of the refugees women are involved in agriculture, more land be allocate to them and their skills enhanced through training .*Corresponding AuthorISSN 2790-1394KURJpp. 4 - 20Vol 2. Issue 2. Oct 2023Keywords: Financial inclusion, Women refugees, Nakivale refugee settlementmabbas@kab.ac.ugIntroductionForced displacement of people from their motherland is a serious and surging challenge globally Th e UNHCR global trend report 2021 (UNHCR, 2022) reveals that the numbers of people forced to fl ee their homes have been increasing every year for a decade. For instance, the number of people displaced by persecution, war, human rights abuse and violence stood at 89.3 million by the end of 2021 and increase of eight percent from 2020 (UNHCR, 2022). With the emergency of new conflict zones such as the Ukraine-Russian war and putschist surges in Africa, the progressive increase in a number of displaced people is definite. Earlier statistics indicate that in 2019, an estimated 11.0 million people were newly displaced, while 2.4 million sought protection outside their country, while 8.6 million were displaced within the borders of their countries UNHCR (2020). Many displaced populations failed to fi nd long-lasting solutions for rebuilding their lives. Most refugees live in temporary camps established as an institution to give people protection in cases of emergency (Dela Chaux & Haugh, 2014).